Die akute lymphatische Leukämie – Diagnostik, Subgruppen und Therapien - Wermann, Wiba Keke; Gökbuget, Nicola (DMW - Deutsche Medizinische Wochenschrift, 2018)
The acute lymphoblastic leukemia (ALL) is a heterogenous rare malignant disease of lymphoblastic precursor cells. The peak of incidence lies in childhood (5.3/100 000), but the incidence rises again from the age of 50 onwards, showing a second peak at patients > 80 years old (2.3/100 000). The ALL is an acute life-threatening disease which untreated leads to death within a short time. The therapeutic objective is cure. By the characterization of subgroups, their targeted therapy and therapy optimization cure rates could be improved (from less than 10 % in the eighties) to more than 50 – 70 % (depending on the subgroup). To this achievement the approach has contributed with risk adapted therapy protocols, with improved supportive therapy and in particular with taking the minimal residual disease (the most important prognostic factor) as a basis for the therapy decision. Recently, with the new immunotherapies there exist further promising options of targeted therapies.
Keywords: Akute lymphatische Leukämie; Chemotherapie; Stammzelltransplantation; Prognosefaktoren